Pushing the asphalt recycling technology to the limit - Oliveira, Joel (2013)
The environmental and economic benefits of using Reclaimed Asphalt Pavement (RAP) material in hot mix asphalt (HMA) applications could be pushed up to the limit, by producing totally recycled HMAs (100% RAP), but the performance of this alternative must be satisfactory. In the present study, the utilization of a used motor oil as a rejuvenator was evaluated. This would allow the aged binder to restore some of its original properties, thus promoting an adequate performance of the mixture. After studying the RAP moisture content, the optimal amount of oil was determined by conventional bitumen tests, using the penetration grade as the selection criterion. Then, the binder was evaluated through rheological testing, and laboratory specimens were prepared and tested for water sensitivity, permanent deformation, stiffness and fatigue, in order to confirm that the totally recycled mixture will perform as good as a conventional mixture used for comparison purposes.